PENGALAMAN NEGERI KELANTAN DALAM MELAKSANAKAN HUKUMAN SEBAT ROTAN TERHADAP KESALAHAN JENAYAH SYARIAH - Ismail, Siti Zubaidah (Jurnal Syariah, 2019)
Whipping sentence is hardly imposed on shariah offenders even though its provision is clearly stated under certain offences. Some states in Malaysia have the provision in sound and clear terms but implementation wise, Kelantan is ahead of her counterparts because aggressive action, taken right after the codification of the Shariah Criminal Enactment in 1985, not only proved to be a wise step but also lead Kelantan to be an exemplary state where whipping sentence is concerned. This article elaborates the systematic implementation of the sentence by referring to the low-profile Whipping Rules of 1987 and the newly enacted Shariah Criminal Procedure Enactment 2002. It is found that other states can also put into practice the theoretical provisos and no need to shy away from Kelantan should they feel that it is timely to flog the offenders in their states.